Vibration control in semi-active suspension of the experimental off-road vehicle using information about suspension deflection - Kasprzyk, Jerzy; Krauze, Piotr; Budzan, Sebastian; Rzepecki, Jarosław (Archives of Control Sciences, 2017)
Abstract The efficiency of vibration control in an automotive semi-active suspension system depends on the quality of information from sensors installed in the vehicle, including information about deflection of the suspension system. The control algorithm for vibration attenuation of the body takes into account its velocity as well as the relative velocity of the suspension. In this paper it is proposed to use the Linear Variable Differential Transformer (LVDT) unit to measure the suspension deflection and then to estimate its relative velocity. This approach is compared with a typical solution implemented in such applications, where the relative velocity is calculated by processing signals acquired from accelerometers placed on the body and on the chassis. The experiments performed for an experimental All-Terrain Vehicle (ATV) confirm that using LVDT units allows for improving ride comfort by better vibration attenuation of the body.